Design, Synthesis and Preliminary Antimicrobial Evaluation of New Derivatives of Cephalexin - Shakir M. Alwan; Sarrah S. Jabbar (College of Pharmacy University of Baghdad, 2017)
There is a continuous and massive need for newer cephalosporins that should have resistance against Î²-lactamases and can be used orally. An approach of using cephalexin, as a well-studied and potent antibacterial compound is considered to prepare new designed derivatives.  These derivatives include the incorporation of amino acid moiety linked through an amide bond with the Î±-amino group of cephalexin. Certain aliphatic amino acids were used, such as glycine, alanine, valine and proline. The chemical structures of these derivatives were confirmed by IR spectroscopy and elemental analyses. All the synthesized compounds were subjected for preliminary evaluation of antimicrobial activity using well diffusion method, against certain microbes. Most of the synthesized compounds were found to possess significant antibacterial activities.  Compound 1 (125 Î¼g and 250Î¼g) showed significant activity against P. aeruginosa. Compound 2 (125 and 250Î¼g) exhibited significant activity against P. aeruginosa and Bacillus cereus.  Compound 3 (125 and 250Î¼g) demonstrated very significant activity against E. coli, P. aeruginosa and Bacillus cereus and slight activity towards S. aureus. Compound 4 (250Î¼g) showed significant activity against P. aeruginosa and no antibacterial activities against E. coli, S. aureus and Bacillus cereus, as compared with cephalexin as the standard compound. Keywords: Cephalosporins, Cephalexin, Glycine, Alanine, Valine, Proline.